Development of a time-resolved fluorescence immunoassay kit for detecting canine coronavirus and parvovirus through double labeling - Laiqing Li; Cuicui Chen; Huankun Liang; Wenqi Dong; V. N. Leontiev; Igor Vitalievich Voytov (Virology Journal, 2024)
Abstract Objective Canine enteric coronavirus (CCV) and canine parvovirus type 2 (CPV-2) are the main pathogens responsible for acute gastroenteritis in dogs, and both single and mixed infections are common. This study aimed to establish a double-labeling time-resolved fluorescence immunoassay (TRFIA) to test and distinguish CCV and CPV-2 diseases. Methods A sandwich double-labeling TRFIA method was established and optimized using europium(III) (Eu3+)/samarium(III) (Sm3+) chelates. CCV/CPV-2 antigens were first captured by the immobilized antibodies. Then, combined with Eu3+/Sm3+-labeled paired antibodies, the Eu3+/Sm3+ fluorescence values were detected after dissociation to calculate the CCV/CPV-2 ratios. The performance, clinical performance and methodology used for laboratory (sensitivity, specificity, accuracy and stability) testing were evaluated. Results A double-label TRFIA for CCV and CPV-2 detection was optimized and established. The sensitivity of this TRFIA kit was 0.51 ng/mL for CCV and 0.80 ng/mL for CPV-2, with high specificity for CCV and CPV-2. All the accuracy data were less than 10%, and the recovery ranged from 101.21 to 110.28%. The kits can be temporarily stored for 20 days at 4 °C and can be stored for 12 months at temperatures less than − 20 °C. Based on a methodology comparison of 137 clinically suspected patients, there was no statistically significant difference between the TRFIA kit and the PCR method. Additionally, for CCV detection, the clinical sensitivity was 95.74%, and the clinical specificity was 93.33%. For CPV-2 detection, the clinical sensitivity was 92.86%, and the clinical specificity was 96.97%. Conclusion In this study, a double-label TRFIA kit was prepared for CCV and CPV-2 detection with high laboratory sensitivity, specificity, accuracy, stability, clinical sensitivity and specificity. This kit provides a new option for screening/distinguishing between CCV and CPV-2 and may help improve strategies to prevent and control animal infectious diseases in the future.